Structural characterisation and in vitro behaviour of apatite coatings and powders. - Etok , Susan E. (Faculty of Medicine and Biosciences, 2009)
Hydroxyapatite (HAP) coatings are used in orthopaedic surgery for bone regeneration. Current methods of phase quantification of HAP coatings suffer from drawbacks. A novel methodology of quantitative phase analysis of HAP coatings has been devised and validated. This method, based on whole pattern fitting with a fundamental parameters approach, incorporates amorphous calcium phosphate (ACP) and apatite phases into structural refinements. A comparison of the structural and chemical properties of plasma sprayed (PS) and novel electrodeposited (ED) HAP coatings has been conducted. ED coatings contained less ACP and more preferred orientation than the PS coatings, although the stoichiometry was similar. In vitro investigations of PS and ED coatings in simulated body fluid and foetal calf serum revealed that both are bioactive. A carbonated apatite layer produced on the ED coatings was -0.7μm thick with a stoichiometry and chemical constituents similar to that of natural bone apatite. PS coatings produced a nanocrystalline carbonated apatite layer (-4μm). For the first time it has been possible to model crystalline HAP and nanocrystalline apatite as independent phases and obtain accurate lattice parameters for each. A positive linear correlation has been made between microstrain and the solubility of HAP and carbonated apatites. Dissolution studies have shown that the behaviour of HAP and carbonated apatite is dominated by crystallite size at low undersaturation and by crystallite size and microstrain at high undersaturation for crystallites between -30OA- 1000A. Metastable equilibrium occurred for crystallites <_400A at low undersaturation. Carbonate content did not affect the solubility or dissolution behaviour. A novel technology for coating polymeric tape with HAP for potential use in anterior cruciate ligament reconstruction has been devised. Mechanical tests have demonstrated that no adverse properties are induced by the coating technology. Cell culture studies have shown that the HAP layer is capable of enhanced attachment, proliferation and differentiation of osteoblast cells compared to uncoated tape.
Keywords: Nanostructured materials; Supramolecular chemistry; Biomimetic Materials - chemical synthesis; Biocompatible Materials; Macromolecular Substances; Nanostructures; Nanotechnology - methods; Structural characterisation; In vitro analysis; Apatite